Effect of dorsal and ventral hippocampal lesions on contextual fear conditioning and unconditioned defensive behavior induced by electrical stimulation of the dorsal periaqueductal gray. - Carolina Irurita Ballesteros (Public Library of Science (PLoS), 2014)
The dorsal (DH) and ventral (VH) subregions of the hippocampus are involved in contextual fear conditioning. However, it is still unknown whether these two brain areas also play a role in defensive behavior induced by electrical stimulation of the dorsal periaqueductal gray (dPAG). In the present study, rats were implanted with electrodes into the dPAG to determine freezing and escape response thresholds after sham or bilateral electrolytic lesions of the DH or VH. The duration of freezing behavior that outlasted electrical stimulation of the dPAG was also measured. The next day, these animals were subjected to contextual fear conditioning using footshock as an unconditioned stimulus. Electrolytic lesions of the DH and VH impaired contextual fear conditioning. Only VH lesions disrupted conditioned freezing immediately after footshock and increased the thresholds of aversive freezing and escape responses to dPAG electrical stimulation. Neither DH nor VH lesions disrupted post-dPAG stimulation freezing. These results indicate that the VH but not DH plays an important role in aversively defensive behavior induced by dPAG electrical stimulation. Interpretations of these findings should be made with caution because of the fact that a non-fiber-sparing lesion method was employed.